Central Bank Balance Sheet, Liquidity Trap, and Quantitative Easing - Tiago C. Berriel; Arthur Mendes (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2015)
We show that, when a central bank is not fully financially backed by the treasury and faces a solvency constraint, an increase in the size or a change in the composition of it's balance sheet (quantitative easing) can serve as a commitment device in a liquidity trap scenario. In particular, when the short-term interest rate is in zero lower bound, open market operations by the central bank that involve purchases of long-term bonds can help mitigate deflation and recession under a discretionary policy equilibrium. This change in central bank balance sheet, which increases its size and duration, provides an incentive to the central bank to keep interest rates low in future in order to avoid losses and satisfy its solvency constraints, approximating its full commitment policy.Creation-Date: 2015-05-08
Keywords: 330